A sequential, integrated, sustainable organisationstakeholder relationship (SISOSR) process for building organisation-stakeholder partnerships - Yolandi Slabbert; Rachel Barker (Communicare)
Although the concept ‘organisation-stakeholder relationship (OSR)’ is not new and has been researched extensively in the literature, few attempts have been made to critically analyse existing viewpoints and propose a unified conceptual framework. The main research problem of this paper is to address this lack of a commonly accepted conceptual framework for organisational stakeholder relationships. This is done through a critical analysis of the different perspectives and existing conceptual frameworks, using a qualitative method whereby strategic stakeholder identification, OSR development, and OSR maintenance are integrated to propose a conceptual framework, subsequently termed SISOSR, for building organisation-stakeholder partnerships (OSPs) with strategic stakeholders. This article is structured as follows: Firstly, the key concepts are defined; secondly, the building blocks of the framework are presented based on sound theoretical constructs; and. thirdly, the SISOSR framework is graphically presented and discussed to elaborate on the proposed process of OSR building, followed by concluding arguments.